Fibromyalgia and Irritable Bowel Syndrome in Female Pelvic Pain - Johnson, Christina M.; Makai, Gretchen E. H. (Seminars in Reproductive Medicine, 2018)
Fibromyalgia and irritable bowel syndrome are common disorders which often coexist in women with chronic pelvic pain. Like pelvic pain, these disorders describe symptoms without pathologic findings. Women with chronic pelvic pain have a higher prevalence of fibromyalgia (4–31%) and irritable bowel syndrome (8–41%) than the general population. Aberrant pain processing and psychosocial stressors are implicated in the co-occurrence of these pain syndromes (chronic overlapping pain conditions), but active epidemiologic, psychosocial, and neurobiologic research is ongoing. Given the higher prevalence of fibromyalgia and irritable bowel syndrome in women with chronic pelvic pain, gynecologists should have more education in diagnosis and treatment of these and other chronic overlapping pain conditions to improve care for women.
Keywords: fibromyalgia; irritable bowel syndrome; pelvic pain